Teachers' Profesional Competence In Teaching Arabic As A Foreign Language In Secondary Schools: A Praxeology Perspective - Nurbayan, Yayan; Sanusi, Anwar; Ali, Mad; Ismail, Zawawi bin; Nurmala, Mia (Ijaz Arabi Journal of Arabic Learning, 2025)
In teaching Arabic, the professional competence of Arabic teachers (AT) is an aspect that today's teachers must possess. Moreover, teaching Arabic in the 21st century emphasizes the communication skills of educators when using a foreign language. Therefore, this study aims to investigate the professional competence of AT in terms of praxeology perspectives, which include three cycles: the see cycle, the act cycle, and the judge cycle. This study uses a qualitative approach with a case study design. The study was conducted in three secondary schools (Madrasah Aliyah) in the Bandung Raya area, West Java. Participants in this study were nine AT. The study results showed that of the nine AT with a vision and mission of teaching based on multilingualism, only AT 1, AT 5, and AT 8. In the see cycle, three AT envisioned improving students' Arabic communication skills with a cultural approach, technology, and interactive methods. In diagnosing student difficulties, teachers used methods such as questions and answers, discussions, and conversation simulations, with the main challenges faced by students being a lack of vocabulary, sentence structure, and speaking anxiety. Then, in the act cycle, three AT showed variation in the application of learning methods and consistently used a multilingual approach. In addition, teachers explained the differences in Arabic and other foreign language structures and corrected students' mistakes in pronunciation and grammar. In the judge cycle, after an evaluation, three AT improved by adjusting teaching methods, such as increasing conversation exercises, adding project-based assignments, or utilizing learning technology.